COMPARISON OF MACROZOOBENTHOS ABUNDANCE BETWEEN COASTAL AND MANGROVE AREAS OF TANJUNG LIMAU KUTAI KARTANEGARA DISTRICT - Simanihuruk, Dorsen Hotma Tua; Paputungan, Mohammad Sumiran; Ritonga, Irwan Ramadhan (Universitas Mataram, 2025)
Macrozoobenthos have played an important role in coastal ecosystems, especially in beaches and mangrove areas, as indicators of environmental health and as important components of the food chain. However, the presence of human activities such as industrial waste, households, fisheries and agriculture could affect the abundance of macrozoobenthos in coastal areas. The purpose of this study was to assess and analyze the type, abundance, diversity, uniformity and dominance of macrozoobenthos and sediment substrate conditions in the beach and mangrove areas in Tanjung Limau village, Kutai Kartanegara Regency. This research was conducted from December to March 2024. This research method uses descriptive methods with sampling techniques using purposive random sampling. Macrozobenthos sampling sites were divided into 2 (two) stations. Station 1 was located at beach area, while station 2 was located in the mangrove ecosystem area. The results showed that the abundance of macrozoobenthos in the mangrove area (13 species) was higher compared to the beach (18 species), with groups of snails and bivalves. Abundance at station 1 (43.3 ind/m²) was lower than at station 2 (58.0 ind/m²). The diversity index value at station 1 (2.16) and station 2 (2.57) was classified as moderate. Uniformity at stations 1 and 2 was 0.84 and 0.87 (high category), respectively. Then the dominance index values found at stations 1 and 2 were 0.17 and 0.10 (non-dominant category), respectively. The sediment texture in the coastal area of Tanjung Limau at both stations 1 and 2 is a clayey loam, which is one of the main causes of the differences in macrozoobenthos abundance.